The Effect of Adding Egg Shells to Moist Feed on The Specific Growth and Survival Rate of Lobster Panulirus sp - Achmad, Marlina; Widarma, I Gede Shindu; Fadilah, Mifta Nur; Ramadhan, Riski; Putri, Siti Arleneyanti (Torani Journal of Fisheries and Marine Science, 2021)
Sea lobster is a commodity that has high value in both national and international markets. Globally, the demand for sea lobster is increasing by about 15% per year. During growth, lobsters undergo a moulting process. Moulting/ecdysis is a very important process in the life cycle of arthropods (including decapods) because shell release is a must for growth and metamorphosis. In improving and assisting the molting process in lobsters, it is assisted by the provision of additional calcium from egg shells. Egg shells contain 94% calcium carbonate, 1% calcium phosphate, 1% magnesium carbonate and 4% organic compounds. In this study, an experiment was conducted on the addition of feed with a mixture of egg shells to support post-moulting optimization and supplement calcium requirements for lobster larvae. The percentage of egg shells as treatment, namely treatment A (0%), B (5%), C (10%), and D (15%) of the total feed to be made for sea lobster. Maintenance is carried out in a controlled tub, for four months. The highest specific growth obtained in this treatment was treatment A (0.06-0.21%) and the lowest was treatment D (-0.02%)-(-0.37%). Furthermore, the highest survival rate was obtained in treatment A (66.7%) and the lowest in treatment D (33.3%), the highest number of molting lobsters was in treatment A (77.8%) and the lowest was treatment D (33.3%). This shows that the addition of eggshell flour to moist lobster feed has not had a significant effect. For further development, it is necessary to research related to the use of additional ingredients in moist feed for lobster.